Analisis gaya kepemimpinan, budaya organisasi, dengan kepuasan kerja sebagai variabel intervening terhadap kinerja karyawan - Rindi Wirawati Putri (UPAJIWA, 2020)
This research was aimed to investigated: 1). Effect of Leadeship Style on employee job satisfication of CV. Mangrove International 2) Effect of Organizational culture on employee Job Satisfication of CV Mangrove InTERNATIONAL 3. Effect of Leadership Style on Employee Performance of CV. Mangrove International 4). Effect of Organizational Culture on Employee Performance of CV. Mangrove International 5). Effect of Leadership Style combined with Employee Satisfication of CV Mangrove International, 6). Effect of Leadership style combined with Organizational Culture on Employee Performance, 7). Effect of Empoyee Satisfication on Empoyee Performance of CV Mangrove International. This research used sensuse sampling methode in all population, sample that used was 50 respondent. Data that be used was primary data from quistionare. Analysis tool instrument in this research using SPSS for windows 17.0 and Analysis tool inferential using patial least Square (PLS) which is SEM variance basis with software Smart PLS 3.0. The result showed that: 1). Leadership Style gives significantly positive effect on employee satisfication of CV. Mangrove International with 0,022 P-value and 0,402 parameter of coeficient. 2). Organizational Culture gives non significantly negative effect on employee satisfication of CV Mangrove International with 0,603 P-Value and -0,094 parameter of coeficient. 3. Leadership Style gives non significantly negative effect on employee performance of CV Mangrove International with 0,89 P-Value and -0,026 Parameter of Coeficient. 4). Organizational Culture gives non significantly negative effect on employee performance of CV Mangrove International with 0,175 P-Value and -0,274 parameter of coeficient. 5)Leadership Style simultan combined with Organizational Culture gives non significantly positive effect on employee satisfication of CV Mangrove International with 0.193 P-Value and 0,0167 R-Square 6). Leadership Style simultan combined with Organizational Culture gives non significantly positive effect on employee performance of CV Mangrove International with 0,282 P-Value and 0,091 R-Squarre 7). Employee satisfication gives non significantly positive effect on employee performance of CV Magrove International with 0,503 P-Value and 0,11 parameter of coeficient 8) All effect of Leadership style variable with mediation of employee satisfication gives non significanly positive effect on employee performance of CV Mangrove International. Keywords: Analysis of Leadership Style, Organizational Culture, and Job Satisfaction ,empoyee performance.